2011
DOI: 10.1248/bpb.34.160
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Aldose Reductase by Phenylethanoid Glycoside Isolated from the Seeds of Paulownia coreana

Abstract: Aldose reductase (AR) inhibitors have considerable therapeutic potential against diabetic complications and do not increase the risk of hypoglycemia. Through bioassay-guided fractionation of the 70% acetone extract obtained from Paulownia coreana seeds, phenylpropanoid glycosides (compounds 1-4) and 5 phenolic coumpounds were isolated (compounds 5-9). Their structures were determined on the basis of spectroscopic analysis and comparison with reported data. All the isolates were subjected to in vitro bioassays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 19 publications
(17 reference statements)
0
27
0
Order By: Relevance
“…Compound 131 was found to significantly inhibit recombinant human aldose reductase with an IC 50 value of 9.72 µM. Furthermore, it inhibited sorbitol formation in a rat lens incubated with a high concentration of glucose [104]. Meanwhile, the effect of pure PhG on improving glucose tolerance was also performed in vivo and in vitro.…”
Section: Enzyme Inhibitory Activitymentioning
confidence: 99%
“…Compound 131 was found to significantly inhibit recombinant human aldose reductase with an IC 50 value of 9.72 µM. Furthermore, it inhibited sorbitol formation in a rat lens incubated with a high concentration of glucose [104]. Meanwhile, the effect of pure PhG on improving glucose tolerance was also performed in vivo and in vitro.…”
Section: Enzyme Inhibitory Activitymentioning
confidence: 99%
“…(III), products of this pathway and changes in cofactors balance can be proponent of the cellular stress that occurs in diabetes (6,7) and some studies have shown the relationship between increased activity of ALR2 and diabetes chronic complications (8)(9)(10). ALR2 is the first and rate-limiting enzyme in polyol pathway, therefore, it is considered as an important potential therapeutic against diabetes chronic complications (11)(12)(13). A number of ALR2 inhibitors (ARI) have shown the potency of attenuation or prevention of diabetes chronic complications in animal models (14,15), and some of them have been investigated in clinical trials (16,17), but yet most of them have limited success and some of them have severe side effects and low target penetrating (13,(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…ALR2 is the first and rate-limiting enzyme in polyol pathway, therefore, it is considered as an important potential therapeutic against diabetes chronic complications (11)(12)(13). A number of ALR2 inhibitors (ARI) have shown the potency of attenuation or prevention of diabetes chronic complications in animal models (14,15), and some of them have been investigated in clinical trials (16,17), but yet most of them have limited success and some of them have severe side effects and low target penetrating (13,(18)(19)(20). The most current classes of synthetic ARI evaluated in phase-III trials are carboxylic acid inhibitors (zopolrestat, ponalrestat and tolerestat) and spiroimide inhibitors (sorbinil); the former have shown low target permeability and are not efficacious in vivo and the latter although have better target penetrating ability but, have shown skin reaction and liver toxicity (15,21,22).…”
Section: Introductionmentioning
confidence: 99%
“…It has been used for making conventional wood furniture, in landscape architecture, as insecticide agents, and in traditional Korean medicines and home remedies (Kim et al, 2011).…”
Section: Introduction 1)mentioning
confidence: 99%
“…Cho et al (2012) isolated geranylated flavonoid and showed that the methanol extract had potent inhibitory activity against cholinesterase. Kim et al (2011) isolated phenylpropanoid glycoside and five phenolic compounds through bioassay-guided fractionation of 70%-acetone extract from P. coreana seeds and showed that its aldose reductase effect has considerable therapeutic potential, against diabetic complications. Despite all the above, only few studies have shown RSA such as nitrite scavenging activity (NSA) and ABTS RSA, particularly studies on Rancimat tests by using P. coreana extracts.…”
Section: Introduction 1)mentioning
confidence: 99%